THE INFLUENCE OF PERCEIVED EASE OF USE, TRUST AND SECURITY ON INTENTION TO USE E-WALLET - Suryati Suryati; Ika Yoga (IAIN Surakarta, 2021)
The development of transaction payment systems in Indonesia in the form of cashless or electronic presents E-Wallet as a wallet in the form of a smartphone application and connected to a server. The presence of this system must meet the needs of the community, especially related to convenience, trust and security guarantees. The purpose of this study is to determine the influence of perceived ease of use, trust, and the security of Intention to use e-wallet as a fintech economy. This study used the quantitative method. By using primary data, the sample was taken from 180 respondents of GenBI Solo who have transacted using the e-wallet. The sample was taken by using simple random sampling technique. The collecting data method was using questionnaires. The collected data were analysed by using SPSS for windows version 2.5. The result of the study shows that the perceived ease of use influences significant Intention to use e-wallet, trust influences significant Intention to use e-wallet, and security influences significant Intention to use e-wallet.